Novel Implant Coating Agent Promotes Gene Expression of Osteogenic Markers in Rats during Early Osseointegration - Bougas, Kostas; Jimbo, Ryo; Xue, Ying; Mustafa, Kamal; Wennerberg, Ann (International Journal of Biomaterials, 2012)
The aim of this study was to evaluate the early bone response around laminin-1-coated titanium implants. Forty-five rats distributed in three equally sized groups were provided with one control (turned) and one test (laminin-1-coated) implant and were sacrificed after 3, 7, and 21 days. Real-time reverse-transcriptase polymerase chain reaction was performed for osteoblast markers (alkaline phosphatase, runt-related transcription factor 2, osteocalcin, type I collagen, and bone morphogenic protein 2), osteoclast markers (cathepsin K and tartrate-resistant acid phosphatase), inflammation markers (tumor necrosis factor α, interleukin 1β and interleukin 10), and integrin β1. Bone implant contact (BIC) and bone area (BA) were assessed and compared to the gene expression. After 3 days, the expression of bone markers was higher for the control group. After 7 days, the expression of integrin β1 and osteogenic markers was enhanced for the test group, while cathepsin K and inflammation markers were down-regulated. No significant differences in BIC or BA were detected between test and control at any time point. As a conclusion, implant coating with laminin-1 altered gene expression in the bone-implant interface. However, traditional evaluation methods, as histomorphometry, were not adequately sensitive to detect such changes due to the short follow-up time.